Geobotanical Study and Preservation of Rare and Endangered Rosaceae Species - Natalya V. Romadanova; Alina S. Zemtsova; Nazira A. Altayeva; Natalya A. Artimovich; Alyona M. Alexandrova; Svetlana V. Kushnarenko; Jean Carlos Bettoni (Plants)
The loss of plant species, especially endangered and endemic ones, poses a significant threat to global biodiversity. These species cannot easily be replaced when their populations decline or become extinct, which makes their loss particularly devastating. This study focuses on the geobotanical study of nine Rosaceae species (Cotoneaster karatavicus, Crataegus ambigua, Malus niedzwetzkyana, Malus sieversii, Prunus tenella, Prunus ulmifolia, Sibiraea laevigata, Sorbus persica, and Spiraeanthus schrenkianus) and the development of ex situ approaches for the conservation of Rosaceae species listed in the Red Book of Kazakhstan. The geobotanical study revealed an alarming trend of biodiversity loss in five regions of Kazakhstan. This loss is driven by threats from diseases and pests, as well as the aging of plants, small population sizes, weak in situ fruiting, and other factors, such as climate change. We have established an in vitro collection for the short- and medium-term conservation of seeds, embryos and shoots taken either directly from field-grown plants or from budwood cuttings forced indoors. We also use long-term sexual conservation methods, such as the cryopreservation of seed and embryonic axes, alongside conventional seed banking at −20 °C. Ex situ conservation efforts that use multiple propagules and storage methods for the same species are well-suited to a diverse genebank facility. These efforts enable future generations to use this valuable reservoir of genetic diversity for crop improvement and may also serve as a basis for propagating planting material to restore degraded populations.